2018
DOI: 10.1038/s41598-018-31087-0
|View full text |Cite
|
Sign up to set email alerts
|

NEC is likely a NETs dependent process and markers of NETosis are predictive of NEC in mice and humans

Abstract: Necrotizing enterocolitis (NEC) is one of the most devastating diseases affecting premature and mature infants. It is hypothesized that NEC is the result of neutrophils’ active role in hyperinflammation after bacterial gut colonization, through their nuclear DNA release and formation of neutrophil extracellular traps (NETs) to combat pathogens. The aim of this study was to evaluate the importance of NETs in NEC pathogenesis, as well as to identify and validate markers of NETosis to predict NEC. NEC was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 43 publications
2
72
0
1
Order By: Relevance
“…Hence, in our study we also explored the ability of several markers of neutrophil activation, in order to identify PDAC and DECC patients at high risk of developing VTE during follow-up. To that end, we measured different plasma markers of neutrophil activation following the strategy addressed in previous studies [51][52][53][54][55][56][57]. We have observed an increase in calprotectin and MPO plasma levels in those patients who developed VTE compared with those who did not.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence, in our study we also explored the ability of several markers of neutrophil activation, in order to identify PDAC and DECC patients at high risk of developing VTE during follow-up. To that end, we measured different plasma markers of neutrophil activation following the strategy addressed in previous studies [51][52][53][54][55][56][57]. We have observed an increase in calprotectin and MPO plasma levels in those patients who developed VTE compared with those who did not.…”
Section: Discussionmentioning
confidence: 95%
“…Different markers of neutrophil activation were measured in every plasma sample obtained during follow-up from the 32 patients studied herein, following the strategy addressed in previous studies [51][52][53][54][55][56][57]. Cell-free DNA (cfDNA; Quant-iT PicoGreen dsDNA kit, Life Technologies, Eugene, OR, USA) and nucleosomes (Cell Death Detection ELISA PLUS kit, Roche, Mannheim, Germany) were measured as markers of the nuclear content of neutrophils released by neutrophils upon NETosis.…”
Section: Quantification Of Neutrophil Activation Markersmentioning
confidence: 99%
“…Data on human histology also showed that immunothrombosis is present in NEC and this can lead to interesting research developments. 30 Elevated circulating cfDNA levels in neonatal plasma have been associated at late-onset sepsis diagnosis and few days before NEC. 31 It is therefore clear that insights into NEC would prove useful for several reasons: (i) it may help develop a treatment for a disease which is still linked to a very high mortality rate; 32 (ii) it may represent a model to further investigate severe immunothrombosis in neonates as most of the interactions between inflammation, immunity and coagulation occur in the gut; (iii) since severe thrombosis of the mesentery is a common finding in NEC, further investigation may determine whether treatment against NETosis can selectively reduce thrombus formation and maintain blood supply to the gut.…”
Section: Necrotising Enterocolitismentioning
confidence: 99%
“…Recent studies evaluating neonatal, and not umbilical cord blood, surrogate markers of NET formation showed an association with sepsis (25,26): elevated circulating cfDNA levels in neonatal plasma have been associated with late-onset sepsis, as well as necrotizing enterocolitis, diagnosis (25). Moreover, neutrophils capable of releasing NETs have also been described as potential sepsis biomarkers in neonates (11,26).…”
Section: Discussionmentioning
confidence: 99%
“…When released from neutrophils during infection, the proteins and chromatin contained within the NETs form a protective mesh that filters and destroys pathogenic organisms (6). However, NET formation also occurs inappropriately during sterile inflammation resulting in thrombosis, autoimmunity, and tissue damage for instance after ischemia perfusion injuries (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%